The Relationship of Electricity Consumption, Export, and Economic Growth in ASEAN - Chanchamroeun Kuoch (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
In this paper, the author explores the relationship of electricity consumption, export, and economic growth of eight ASEAN countries over the period 1995-2011 by using the panel ARDL approach. To date, there are no other studies that explore estimations between economic growth and determinant factors. This will be the first paper to produce the estimation among economic growth, electricity consumption, and export by employing PMG and MG estimators. In this research there are four steps of methodology. First the panel unit root tests are used to test the stationary of those variables. Second, the author used Pool Mean group (PMG) estimator and Mean Group (MG) estimator to estimate the short and long run relation among those variables. Then, Hausman test is used to choose the best estimator between PMG and MG. Last but not least, Fully Modified Ordinary Least Square (FMOLS) which proposed by Pedroni (2000) in this paper that estimate the coefficient of each panel group. The macroeconomic variables are lnGDP, lnEC, lnEX, lnK, and lnL. The author proposes to use some methods to test the unit root namely LLC (2002), Im, Pearan and Shin (2003), and Maddala and Wu (1999). There are two steps of using the method in this research; first, Pesaran (1999) introduced the Hausman test to test the hypothesis of inconsistency of an estimator. After using the Hausman test, the results show that there is a long run relation between economic growth and determinant factors by using PMG. Additionally, in the short run export and labor have a positive relation to economic growth; export and electricity consumption will lead economic growth in ASEAN. Furthermore, the author also used the Fully Modified Ordinary Least Square (FMOLS) method to test the cointegration of those panel data. The empirical result shows that electricity consumption, export, and capital are significance so that the increase of electricity consumption, export, and capital can improve the economic growth in ASEAN. This paper will be useful for governments and other researchers to explore further about energy and export policy. There are a long run relation among electricity consumption, export, and capital in ASEAN so that electricity consumption, export, and capital are the important engine to improve the economic growth in ASEAN. Government should have appropriate policy to invest in electricity production and improve export in order to improve the economic growth in this region. Furthermore, government should create friendly environment for FDI in order to attract more capital to this region.